Some Contemporary Models of Comparative Politics: Critique, Analysis and Application to Change - Gupta, Roshanlal Kulbushan (My University, 1970)
It is the obiect of this study to investigate how some contemporary modeis of comparative politics deal with the problem of change over time. In addition, an analysis of the models qua models facilitating comparative political analysis will be provided.
Keywords: Political Science; Political Science